Pengaruh Interval Lama Penyungkupan dengan Kombinasi Media Tanam (Tanah, Arang Sekam, Kascing) Terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca Sativa L.) - Aprilia, Tiara; Idris, M (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of long exposure intervals and the combination of planting media on the growth and yield of lettuce (Lactuca sativa L.). The research method used was a Randomized Group Design (RAK) with two factors. The first factor is the exposure interval (S0 = control, S1 = 10 days, S2 = 20 days, S3 = 30 days), and the second factor is the planting medium (P0 = control, P1 = soil + vermicompost 1:1, P2 = soil + husk charcoal 1:1, P3 = soil + husk charcoal + vermicompost 1:1:2, P4 = soil + husk charcoal + vermicompost 1:2:1). Parameters observed included plant height, number of leaves, wet weight, and dry weight. Data analysis used Multivariate ANOVA and the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that a 30 days cover interval (S3) gave the best results on plant height, while a 10 days cover interval (S1) produced the highest number of leaves, wet weight, and dry weight. The planting medium influences plant height and number of leaves, with the best treatment being P3 for plant height and P1 for number of leaves. The best combination was found in S3P3 for plant height and S3P4 for number of leaves, while for wet and dry weight, S1P1 gave optimal results. The conclusion of this research is that a cover interval of 10–30 days and a combination of planting media have a significant effect on the growth and yield of lettuce plants. Keywords: Covering Interval, Combination of Planting Media (Soil, Charcoal Husk, Vermicompost), Lettuce